Costituzione e CEDU nell'evoluzione giurisprudenziale della sfera familiare - MASCIOTTA, COSTANZA (Premio Ricerca «Città di Firenze», 2019)
This volume analyses the judgement techniques and the substantial protection offered by the Italian Constitutional Court and the European Court of Human Rights in the context of 'ethically sensitive' issues, such as medically assisted procreation and homo-affective unions. The investigation touches on different profiles of constitutional law: the multilevel protection between Rome, Strasbourg and common judges; the problematic emergence of 'new rights' in the face of scientific evolution and changing social sentiment; the dynamics between case and statutory law. The author proposes new judging techniques aimed at guaranteeing an effective protection of the interests at stake, as well as at reducing the distances between case and statutory power.